Factor structure of teacher-related boredom in EFL classroom: a mini literature review - Liu, Fang; Cho, Hyonsuk (Frontiers in Education, 2025)
The attention of researchers in the field of second language acquisition has been drawn to boredom, which was considered as one of the most prevalent and distressing emotions. However, studies delving into the teacher-related foreign language boredom are few. Recognizing the significant role of teachers in foreign language education, we aimed to identify the sources and factor structure of teacher-related boredom through a literature review. Drawing on a review of existing literature and control-value theory, five teacher-related factors are identified using both inductive and deductive approaches: teacher controlling teaching, teacher emotional support, teacher-student rapport, teacher feedback, and teacher burnout. A deeper understanding of teacher-related boredom in EFL classrooms can help researchers and educators in the field of second language acquisition gain valuable insights into its contributing factors, inform instructional practices, and improve learner engagement and outcomes.